Yielding behavior of a single-crystalline γ'-strengthened Co-Ti-Cr superalloy. (15th July 2021) - Bezold, A.; Volz, N.; Lenz, M.; Zenk, C.H.; Spiecker, E.; Mills, M.; Göken, M.; Neumeier, S.
Abstract: The anomalous yielding behavior known from Ni3 Al or Ni-base superalloys is explained by the formation of immobile dislocation configurations via cross-slip of the leading superpartial of anti-phase boundary-coupled dislocation pairs. A systematic investigation of the anomalous yielding behavior of a single-crystalline Co-11Ti-15Cr superalloy by transmission electron microscopy revealed the absence of similar sessile dislocation configurations during the initial yielding stage. Shearing of γ' precipitates via superlattice stacking fault formation is the dominant deformation mechanism at the peak temperature. Furthermore, the high density of superlattice stacking faults and their interactions also lead to a pronounced work-hardening anomaly. Graphical abstract: Image, graphical abstract